2014
DOI: 10.1016/j.nicl.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Altered resting-state functional connectivity in patients with chronic bilateral vestibular failure

Abstract: Patients with bilateral vestibular failure (BVF) suffer from gait unsteadiness, oscillopsia and impaired spatial orientation. Brain imaging studies applying caloric irrigation to patients with BVF have shown altered neural activity of cortical visual–vestibular interaction: decreased bilateral neural activity in the posterior insula and parietal operculum and decreased deactivations in the visual cortex. It is unknown how this affects functional connectivity in the resting brain and how changes in connectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 87 publications
3
38
0
Order By: Relevance
“…A study of 10 individuals with bilateral vestibular failure found that they developed significant hippocampal atrophy and associated impairments in visuospatial tasks such as navigation in a virtual maze . Another study in 22 individuals with bilateral vestibular loss found decreases in functional connectivity of temporoparietal junction structures critical for visuospatial processing and the rest of the brain …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 10 individuals with bilateral vestibular failure found that they developed significant hippocampal atrophy and associated impairments in visuospatial tasks such as navigation in a virtual maze . Another study in 22 individuals with bilateral vestibular loss found decreases in functional connectivity of temporoparietal junction structures critical for visuospatial processing and the rest of the brain …”
Section: Discussionmentioning
confidence: 99%
“…10 Another study in 22 individuals with bilateral vestibular loss found decreases in functional connectivity of temporoparietal junction structures critical for visuospatial processing and the rest of the brain. 37 The association between vestibular and cognitive dysfunction may also relate to the influence of the vestibular system on working memory and attentional processes. A significant association was found in factor analyses between vestibular function and the working memory and attention factor, which chiefly included the Forward and Backward Digit Span tasks, which are tests of short-term memory.…”
Section: Discussionmentioning
confidence: 99%
“…BVH patients rely more on other sensory inputs such as vision [62,63,64]. However, an increased visual dependence can result in symptoms of vertigo that are provoked or aggravated by specific visual contexts (e.g.…”
Section: Challenges In Establishing a Diagnosis Of Bvhmentioning
confidence: 99%
“…Therefore, the hippocampus could be one of the main structures in which the cognitive and emotional effects of vestibular loss interact [73,74]. Other parts of the brain show changes in resting-state connectivity due to BVH, which may also account for the persistent deficits in visuospatial attention and spatial orientation as well as unsteadiness [63]. In other words, cognitive deficits can be related to vestibulopathy and should not be disregarded while taking the history of a patient.…”
Section: Challenges In Establishing a Diagnosis Of Bvhmentioning
confidence: 99%
“…However, it may be promising that deafferentation from bilateral peripheral vestibular signals leads to even more fundamental changes: resting‐state activity in the brain, irrespective of any vestibular task, shows profound changes of functional connectivity in BVF patients [Göttlich et al, ]. There was lower bilateral connectivity in the posterior insula and parietal operculum but higher connectivity in the posterior cerebellum.…”
Section: Introductionmentioning
confidence: 99%